2013
DOI: 10.1002/sej.1159
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurship and Strategy in Emerging Economies

Abstract: This is the accepted version of the paper.This version of the publication may differ from the final published version. The world is undergoing a rapid economic shift as firms in the long dominant economies of Europe and North America are increasingly being challenged by firms from emerging economies, firms from low-income, high-growth nations principally are principally reliant on economic liberalization for their growth (Hoskisson, et al., 2000;Wright et al., 2005; Bruton, Ahlstrom, & Li, 2008). The growth of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
121
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 148 publications
(136 citation statements)
references
References 38 publications
2
121
0
3
Order By: Relevance
“…Instead, it serves as a means of crystalizing the effect of other factors. For instance, several researchers have studied the entrepreneurial activities of emerging countries and how they have been able to overcome the limitations of their location and the distance that separates them from global markets (for a review, Zahra, Abdel-Gawad and Tsang, 2011; Bruton et al, 2013). Brazil, for instance, has witnessed a rise in entrepreneurial activities when it took steps to reconnect itself with the rest of the world.…”
Section: Spatial Dimension Of Contextmentioning
confidence: 99%
“…Instead, it serves as a means of crystalizing the effect of other factors. For instance, several researchers have studied the entrepreneurial activities of emerging countries and how they have been able to overcome the limitations of their location and the distance that separates them from global markets (for a review, Zahra, Abdel-Gawad and Tsang, 2011; Bruton et al, 2013). Brazil, for instance, has witnessed a rise in entrepreneurial activities when it took steps to reconnect itself with the rest of the world.…”
Section: Spatial Dimension Of Contextmentioning
confidence: 99%
“…Russia has developed a significant 'shadow economy' that has historically offered alternatives to dealing with more formal institutions. However, accompanying corruption and weak legal institutions has the potential to result in an unproductive 'dark side' of entrepreneurship which forces out productive entrepreneurship and impedes economic development (Bruton et al, 2013). Thus, Russia provides an interesting setting in which to explore the influence of several important regulatory factors upon the manifestation of EO within an emerging economic context.…”
Section: Introductionmentioning
confidence: 99%
“…Second, we assess the validity of the EO measure, developed by Covin and Slevin (1989), in different contexts. As many theories developed in mature markets are challenged when applied to emerging economies (Bruton et al, 2013), this research found evidence of two dimensions of innovativeness/proactiveness and risk-taking in the Russian context. Thus we could argue that in the emerging market data, EO is not a unidimentional latent variable, but rather multidimensional with innovativeness/proactiveness and risk-taking as distinct orbits of potential influence on firm performance.…”
Section: Introductionmentioning
confidence: 74%